PROFESSOR DR. ABD KARIM BOOSTS ONLINE EDUCATION EFFORTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
Though a professor in the field of Food Technology at the School of Industrial Technology Universiti Sains Malaysia (USM), currently Professor Dr. Abd Karim Alias, 53, is more involved in the efforts to boost online educational practices, especially after being appointed as the Director of the Centre for Development of Academic Excellence (CDAE) USM.